Self-awareness assessment during cognitive rehabilitation in children with acquired brain injury: a feasibility study and proposed model of child anosognosia. (23rd October 2015) - Krasny-Pacini, Agata; Limond, Jennifer; Evans, Jonathan; Hiebel, Jean; Bendjelida, Karim; Chevignard, Mathilde
Abstract: Purpose : To compare three ways of assessing self-awareness in children with traumatic brain injury (TBI) and to propose a model of child anosognosia. Method : Five single cases of children with severe TBI, aged 8–14, undergoing metacognitive training. Awareness was assessed using three different measures: two measures of metacognitive knowledge/intellectual awareness (a questionnaire and illustrated stories where child characters have everyday problems related to their executive dysfunction) and one measure of on-line/emergent awareness (post-task appraisal of task difficulty). Results : All three measures showed good feasibility. Analysis of awareness deficit scores indicated large variability (1–100%). Three children showed dissociated scores. Conclusions : Based on these results, we propose a model of child self-awareness and anosognosia and a framework for awareness assessment for rehabilitation purposes. The model emphasizes (1) the role of on-line error detection in the construction of autobiographical memories that allow a child to build a self-knowledge of his/her strengths and difficulties; (2) the multiple components of awareness that need to be assessed separately; (3) the implications for rehabilitation: errorless versus error-based learning, rehabilitation approaches based on metacognition, rationale for rehabilitation intervention based on child's age and impaired awareness component, ethical and developmental consideration of confrontational methods. Implications for Rehabilitation: Self-awareness has multiple components that need to be assessed separately, to better adapt cognitive rehabilitation. Using questionnaires and discrepancy scores are not sufficient to assess awareness, because it does not include on-line error detection, which can be massively impaired in children, especially those with impaired executive functions. On-line error detection is important to promote and error-based learning is useful to allow a child to build a self-knowledge of his/her strengths and difficulties, in the absence of severe episodic memory problems. Metacognitive trainings may not be appropriate for younger children who have age appropriate developmentally immature self-awareness, nor for patients with brain injury if they suffer anosognosia because of their brain injury.